Normative Data for the Low Anterior Resection Syndrome Score (LARS Score). Issue 6 (June 2019) - Juul, Therese; Elfeki, Hossam; Christensen, Peter; Laurberg, Søren; Emmertsen, Katrine J.; Bager, Palle
Abstract : Objective: To provide normative data for the Low Anterior Resection Syndrome (LARS) score. Background: The LARS score is a validated and frequently used tool measuring bowel dysfunction after sphincter sparing surgery for rectal cancer. The interpretation of LARS score results has previously been limited by the lack of normative data. Methods: An age and sex-stratified random sample of 3440 citizens from the general population was drawn from the Danish civil registration system (age range 20–89 years, 50% females). A brief questionnaire including the LARS score and health-related items were distributed electronically or by post. Results: A total of 1875 (54.5%) responded, 54.0% were females. In the age group 50 to 79 years, relevant for most rectal cancer studies, the response rate was 70.5% (n = 807). In this specific age group, 18.8% of the females and 9.6% of the males had a LARS score ≥30, corresponding to the LARS score category "major LARS" ( P = 0.001), and the median (interquartile range) LARS score was 16 (7–26) and 11 (4–22), respectively ( P < 0.001). Responders with physical disease had a statistically significant higher risk of a LARS score ≥30, compared with responders without any physical disease (odds ratio 2.2, 95% confidence interval 1.6–2.9, P < 0.001). Conclusions: A LARS score ≥30 (major LARS) is common in the general population, especially in the age group 50 to 79 years. Normative data for the LARS score are now available and can be taken into account when interpreting LARS score results in scientific studies of bowel function after rectal cancer treatment. Abstract : Supplemental Digital Content is available in the text